Introducing Arabic Letters to Improve Early Childhood Language Skills - Rohmah Sabrina; Biqi Zain biqi (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2025)
The development of language skills in early childhood is a fundamental aspect that needs to be stimulated from an early age, including in learning the Arabic language. This study aims to examine the role of introducing Arabic letters in comprehensively improving the language abilities of young children. The method used is a literature study by analyzing various national and international scientific articles and journals relevant to the topic of introducing hijaiyah letters and early childhood language development. The findings show that introducing Arabic letters through learning methods suited to the characteristics of early childhood such as learning through play, singing, and multisensory approaches, supported by the use of varied and interactive learning media can enhance children’s language skills, including listening, speaking, early reading, and vocabulary acquisition. Thus, the early introduction of Arabic letters can serve as an important foundation for the development of literacy and language abilities in young children.